2020
DOI: 10.1155/2020/8042705
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Markers for Detecting Schistosoma Species by Loop-Mediated Isothermal Amplification

Abstract: Schistosomiasis is considered a neglected parasitic disease. Around 280,000 people die from it annually, and more than 779 million people are at risk of getting infected. The schistosome species which infect human beings are Schistosoma mansoni, Schistosoma haematobium, Schistosoma intercalatum, Schistosoma japonicum, Schistosoma guineensis, and Schistosoma mekongi. This disease is also of veterinary significance; the most important species being Schistosoma bovis since it causes the disease in around 160 mill… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 26 publications
1
15
0
Order By: Relevance
“…A number of LAMP assays have been designed for the species-specific detection of the three main species causing human schistosomiasis ( S. haematobium , S. japonicum and S. mansoni ) and have been applied to schistosomiasis diagnosis, to detect schistosomes-infected snails, and to evaluate efficacy of chemotherapy, both in animal models and human patients. Recently, a LAMP for species-specific detection of the most important veterinary species ( S. bovis ) and a LAMP for simultaneous detection of different Schistosoma species have been also reported [ 31 ]. The selected molecular targets mostly used for LAMP designing for the detection of Schistosoma species are shown in Figure 1 , and different assays features are summarized in Table 1 .…”
Section: Lamp and Schistosomiasismentioning
confidence: 99%
“…A number of LAMP assays have been designed for the species-specific detection of the three main species causing human schistosomiasis ( S. haematobium , S. japonicum and S. mansoni ) and have been applied to schistosomiasis diagnosis, to detect schistosomes-infected snails, and to evaluate efficacy of chemotherapy, both in animal models and human patients. Recently, a LAMP for species-specific detection of the most important veterinary species ( S. bovis ) and a LAMP for simultaneous detection of different Schistosoma species have been also reported [ 31 ]. The selected molecular targets mostly used for LAMP designing for the detection of Schistosoma species are shown in Figure 1 , and different assays features are summarized in Table 1 .…”
Section: Lamp and Schistosomiasismentioning
confidence: 99%
“…In this work, we tested our previously developed species-specific LAMP assays for S. haematobium [ 44 ], S. mansoni [ 45 ], S. bovis and also the genus-specific LAMP for the simultaneous detection of several Schistosoma species [ 42 ] against both gDNA from pure and, for the first time, hybrid schistosomes. These hybrids were obtained in studies conducted in Côte d’Ivoire [ 26 ] and Corsica, France [ 19 ], and subsequently well characterized by amplification and sequencing of a partial fragment of the mitochondrial cytochrome c oxidase subunit 1 (cox1) and the complete nuclear ribosomal DNA internal transcribed spacer (ITS).…”
Section: Discussionmentioning
confidence: 99%
“…LAMP assays were accomplished using the reaction mixtures and specific primer sets previously described elsewhere by our group for detection of species-specific S. mansoni based on a mitochondrial minisatellite DNA region [ 45 ], S. haematobium , based on the ribosomal intergenic spacer (IGS) [ 44 ], and S. bovis , based on the mitochondrial NADH subunit 1 [ 42 ]. A genus-specific LAMP assay designed on the internal transcribed spacer 1 (ITS-1) for the simultaneous detection of different species, including S. mansoni , S. haematobium , S. intercalatum and S. bovis , was also applied [ 42 ]. The reactions were carried out using previously described conditions, with the exception of the final reaction volume, which was reduced from 25 μL to 15 μL.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The ITS-1 [149], IGS [153,156] and DraI [163,164] sequences have been studied for S. haematobium diagnosis, a greater detection limit having been obtained with DraI (0.1 fg). Gandasegui et al [153] worked with the IGS region, finding a larger amount of samples to be positive by colorimetry than by turbidimetry (i.e., when adding SYBR Green I to the reaction); however, the effect of the extraction method has been controversial since Gandasegui et al [153] found that sensitivity was greater when DNA was extracted with a commercial kit.…”
Section: Schistosomiasismentioning
confidence: 99%